Analisis perbedaan risiko likuiditas antara bsi dan bank mandiri periode 2021.q1-2025.q1 - Ariiqoh, Sella Haniifatul (Maliki Interdisciplinary Journal, 2025)
This study examines the differences in liquidity risk between Bank Syariah Indonesia (BSI) and Bank Mandiri for the period Q1 2021-Q1 2025. Using an explanatory comparative quantitative approach with a cross-sectional design. Comparison of FDR (BSI) and LDR (Bank Mandiri) ratios through the Independent T-test. The results show that there is a statistically significant difference between BSI's FDR and Bank Mandiri's LDR. This is due to the operational characteristics of each bank, such as financing mechanisms, product structures, and asset management strategies in the Islamic and conventional systems. Factors related to the characteristics and operational mechanisms of both banking systems. Banking structure, asset quality, economic conditions, monetary policy, market dynamics, and customer needs can influence a bank's ability to determine the differences and levels of liquidity of each bank.